The crane and the keeper : how an endangered crane chose a human as her mate - Pincus, Meeg (Smithsonian kids., 2025)
What was wrong with Walnut? The white-naped crane was friendly and curious -- except when it came to other cranes. Raised by humans, Walnut didn't see herself as a bird and could not live peacefully -- or breed -- with others of her species. Rejected by several zoos, she arrived at the Smithsonian's National Zoo Conservation Biology Institute. Would this be her last chance? Meanwhile, Chris Crowe had also just arrived at the zoo, as crane keeper. It was his job to care for and help breed the birds at the institute. It was clear that breeding Walnut wasn't going to be easy, but with skill and patience, Chris slowly earned the crane's trust, and an extraordinary partnership evolved. In a picture book sure to appeal to wildlife fans -- and anyone who appreciates a unique unlikely friendship tale -- award-winning author Meeg Pincus shares the story of the incredible bond between a crane and her keeper.